Psychosocial safety climate versus team climate: The distinctiveness between the two organizational climate constructs - Lee, Michelle Chin Chin *; Mohd, Awang Idris (Emerald, 2017)
The importance of organizational climates in enhancing employee job performance is well studied in the literature. In this study, by using a multilevel survey, the study investigated the effect of psychosocial safety climate (PSC) and team climate on job performance, particularly through job engagement. The study also predicted that only PSC (and not team climate) predicted job resources (i.e. role clarity and performance feedback). A total of 412 employees from 44 teams (72.6% response rate) in Malaysian private organizations participated in the current study. Research findings revealed that performance feedback and role clarity mediate the relationship between PSC and job engagement, and that there is no direct effect between the variables, team climate and job resources. As expected, the study also discovered that job engagement mediates the relationship between PSC and team climate on job performance. This suggests the importance of PSC as the precursor to better working conditions (i.e. job resources) and to indirectly boosting employees’ engagement and job performance. This paper compared two distinctive organizational climate constructs in affecting the different types of job resources through multilevel approach within the Asian context.